A pesca de covo para peixes na comunidade de Tremembé, Icapuí - CE - Batista, Bruno Damasceno (Universidade Federal Rural do Semi-Árido, 2018)
The present work consists in the description of the fishing with covo for fish in the community of Tremembé, Icapuí - CE. For this, the characteristics of the vessels, the traps and the types of attractors used, as well as the identification of the captured species and respective length distribution were analyzed. The vessels observed in this work were classified into two types, small and medium sized boat. All of them are built in wood, between 9 to 13 meters in length, having diesel engines 60 to 160Hp, and storage of 400 to 8 thousand kilos of fish. The traps used in fishing in the community of Tremembé consist of wooden gratings 120cm long, 110cm wide, 73cm high, trapred by a galvanized wire mesh, but known as a lobster wire, with a 90mm mesh opening. The time of activity of these traps revolves around 10 to 15 days after its launch. The depths of operation of the monitored vessels vary between 15 and 30 meters at a distance of 12 to 20 nautical miles from the community of Tremembé. The number of traps per vessel varies from 35 to 150 units, depending on the type and size of the vessel. Regarding the various types of attractors, the coconut ball is the most used by fishermen. The traps are launched individually without the presence of locating buoys, in it is tied a twisted polyethylene cable of 10mm with 60 meters of length tied to a stone of five kilos, trapped in the lower region where the mouth of the covo is, and in the back region is also placed a cable of 25 meters attached to a garatéia of approximately ten kilograms. This is done to make it easier to find the traps at the time of the drag with a garate. The shipment is carried out in a manual way or by means of mechanical equipment called hoist. The families with the highest number of species captured were Lutjanidae and Haemulidae. The most common species were: mutton snapper (Lutjanus analis), lane snapper (Lutjanus synagris), yellowtail snapper (Ocyurus chrysurus), sailor’s grunt (Haemulon parra), and white grant (Haemulon plumieri). The mean catch sizes of the ariacó (Lutjanus synagris), the cioba (Lutjanus analis) and the guaiúba (Ocyurus chrysurus) were 29.02 cm, 31.3 cm and 40.9 cm, respectively. This shows that some of the main species caught have already been reproduced at least once, showing that the trap fishery in the community of Tremembé, is selective, once that it catch individuals who have reached their first sexual maturity, evidencing sustainable fishing.
Monografia
Keywords: Pesca artesanal; Lutjanidae; Tremembé; Icapuí – CE; Covo; Artisanal fishing; Lutjanidae; Tremembé; Icapuí-CE; Covo; CIENCIAS AGRARIAS::RECURSOS PESQUEIROS E ENGENHARIA DE PESCA